PENGARUH DEBT TO ASSET RATIO, RETURN ON ASSET, TOTAL ASSET TURNOVER DAN CURRENT RATIO TERHADAP PERTUMBUHAN LABA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI TERDAFTAR DI BEI PERIODE 2016 – 2019 - Leslie Jie; Bayu Laksma Pradana (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2021)
This study was conducted to examine the effect of Debt to Asset Ratio, Return on Assets, Total Asset Turnover and Current Ratio on the growth of manufacturing profits in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period of 2016 - 2019. Data collection techniques used were documentation using data secondary. The data analysis method used is a quantitative method with associative and descriptive method approaches. The analysis technique used is multiple regression and hypothesis testing using partial t-test and F test simultaneously. In addition, a classic assumption test which includes a normality test, a multicollinearity test, an autocorrelation test and a heteroscedasticity test are performed. The classic assumption test shows that if this study does not find any distorted variables that meet the requirements of the multiple linear regression equation model. The samples used were 25 companies in 4 periods, 100 samples. The results showed that Total Asset Turnover partially affected earnings growth. Debt to Asset Ratio, Return on Asset, Total Asset Turnover and Current Ratio influence simultaneously earnings growth.